Development of Interactive Media Based on Articulate Storyline with a Culture Responsive Teaching Approach in Spatial Volume Building Material at SD Negeri 01 Sengare, Talun District, Pekalongan Regency - Nailusaulakhah Nailusaulakhah; Aryo Andri Nugroho; Iin Purnamasari (FKIP - Universitas Riau, 2026)
This study aims to develop and assess the quality of interactive multimedia based on Articulate Storyline with a Culturally Responsive Teaching (CRT) approach in spatial volume material in elementary schools. The study used the Research and Development (RnD) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Validation was carried out by subject matter experts and media experts, while practicality and effectiveness were measured through teacher and student questionnaires and pre-tests and post-tests. The results showed that this media was highly valid, with a subject matter expert validation percentage of 92% and media validation of 94%. The practicality of the media was also high, with positive responses from 80% of students and 84% of teachers. The effectiveness test showed a significant increase in student learning outcomes, with an N-Gain value of 0.7143, which is in the high category. These findings confirm that Articulate Storyline-based interactive multimedia that integrates CRT is feasible, practical, and effective for improving mathematical concept understanding, student engagement, and learning outcomes for solid volume material in elementary schools.